Antibiotic resistance of Escherichia coli, according to extended-spectrum beta-lactamase production, in urine cultures. Hospital III-1. Chiclayo, Peru 2020. - Sosa Flores, Jorge Luis (2023)
Objective: to determine the antibiotic resistance of Echerichia coli, in urine cultures, according to ESBL production, in hospitalized patients. The study: Descriptive-retrospective design. Bacterial identification was done with VITEK XL, susceptibility, with the CLSI M100 guidelines. 30 edition. Findings: E. coli ESBL positive, presented 0% resistance to: Meropenem, ertapenem, tigecycline and colistin. Piperacillin/tazobactam, nitrofurantoin, imipenem, amikacin with 16.7%, 6.2%, 5% and 1% respectively. E. Coli ESBL negative, presented 0% resistance to: cefotaxime, cefuroxime, tigecycline and piperacillin/tazobactam. Ceftriaxone, cefepime, gentamicin, cefazolin, ceftazidime, nitrofurantoin, meropenem, amikacin, imipenem, and ertapenem with 14.7%, 13%, 13%, 10.7%, 9.7%, 9.1%, 9.1%, 8%, 5%, 2.7%, respectively. Conclusion: Meropenen, ertapenem, tigecycline, cholesterol, piperacillin/tazobactam, nitrofurantoin, amikacin and imipenem, with less than 20% resistance, were the same for ESBL-positive E. coli, and E. coli, without considering ESBL production.